TECHNOLOGICAL AND PSYCHOLOGICAL ASPECTS OF ECONOMICAL COLLABORATION - Vinogradov, Nick; Savinov, Iliya; Lesnaya, Anastasie (Science-based technologies, 2023)
The technological and psychological aspects of economic cooperation, including international ones, were studied, a comprehensive analysis of the state of the problem was carried out, and the main ways of development of international economic cooperation were outlined. On the basis of the theory of the method of conflict-free management with forecasting the development of the situation, step-by-step authentication of parameters and status, and correction based on the results, a current analysis of the state of mutual relations is proposed. The goal of the work is to maintain a comfortable minimum level of conflict. A comfortable level is understood as one at which the available resources are not less than marginally expendable, and the level of income exceeds the level of unprofitability. It is shown that conflict-free economic cooperation is closely related to the concept of humanitarian economy (humanomics). It has been proven that moral aspects of humanomics in combination with technological mechanisms of conflict management give all parties of economic interaction an additional mutual benefit. Collaboration encourages sales reps to work with each other instead of against each other, leveraging best practices and, in turn, increasing efficiency. In a collaborative situation, sales reps share their best practices and learnings to help the organization succeed as a whole. Everyone in the company has something to say and undoubtedly has some value to contribute. When using methods of managing conflict processes of interaction between partners, success can be achieved, even if the partner does not always have sufficient reserves of resources. Reflexive management achieves solving this task - taking into account the partner's strengths and weaknesses, purposeful restoration of its resources during long periods of conflict-free cooperation. To achieve this goal, the psychological aspects of the partner's behaviour are taken into account in each specific case. According to them, a multi-step strategy of technical and psychological interaction in the economic sphere is being built.